Implementasi Peraturan Walikota Medan 10/2021 untuk Penertiban PKL di Pasar Sukaramai - Hanifah, Alia; Suharyanto, Agung; Simamora, Beltamahmero (Universitas Medan Area, 2025)
This article aims to find out how the Implementation and Obstacles are in Medan Mayor Regulation Number 10 of 2021 Concerning Public Peace and Order at Street Vendors using George Edward III's theory with the variables Communication, Resources, Disposition, and Bureaucratic Structure. The method used in this study is a descriptive qualitative research method using observation, interview and documentation data collection techniques. From the results of the study it can be concluded using variables in Policy Implementation according to George Edward III namely, Communication has been carried out quite well by the PD Pasar by giving warnings in the form of letters but not getting a response from the PKL and still selling on the roadside, Resources that there are still inadequate ones such as a lack of budgetary funds for policing and a lack of land for parking causing traffic jams. The disposition in this study is maximal enough to give a warning letter in the form of an SP to all who violate the regulations but traders still violate it for economic reasons, bureaucratic structure can be said to be quite good because the officers carry out their duties according to the applicable SOP. The obstacle is that there is still a lack of awareness from traders of the existence of rules that should not be violated, but traders still insist on opening stalls on the shoulder of the road and do not accept it when disciplined by officers, but traders who have been disciplined continue to violate existing regulations by never being afraid if someday there will be more control by the existing officers.